Computer-Based Media for Learning Geometry at Mathematics Class of Secondary Schools - Roza, Yenita; Yuanita, Putri; Saragih, Sehatta; Alfajri, Hadiyanta; Saputra, Andespa (Journal of Educational Sciences, 2017)
This research is aimed at developing computer-based media formathematics learning. This media used interactive model to help studentsunderstand the topic of lines, angles and rectangular. This developmentresearch applied development model by Borg and Gallmodified bySugiyono.The study began by finding the potentials materials and itsproblems followed by astudy of literature. The subject in this research isline, angle and rectangular,including rectangle, square and trapezium.Product design was done through two stages: paper-based design   andcomputer-based. The applications used for product design are MicrosoftFrontpage, Microsoft Power Point and Photoshop. Learning media werevalidated by three experts or validators and were revised based on the inputfrom the validators. The revised learning media were tested on two stages: asmall group test consisting of five respondens and a large grouptestconsisting of forty respondens. Based on the analysis of data and discussion,it can be concluded that computer-based mediafor mathematics learning isvalid with an average score of 3.17 on aspect of materials and 3.18 fromaspects of media. This computer-based media formathematicslearning alsohad practicalities with an average score of  97,92% on a small group test and99,22% in the large group test.